2014
DOI: 10.1002/mrd.22357
|View full text |Cite
|
Sign up to set email alerts
|

Transport in technicolor: Mapping ATP‐binding cassette transporters in sea urchin embryos

Abstract: One quarter of eukaryotic genes encode membrane proteins. These include nearly 1000 transporters that translocate nutrients, signaling molecules, and xenobiotics across membranes. While it is well appreciated that membrane transport is critical for development, the specific roles of many transporters have remained cryptic, in part because of their abundance and the diversity of their substrates. Multi-drug resistance ATP-binding cassette (ABC) efflux transporters are one example of cryptic membrane proteins. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 119 publications
(141 reference statements)
3
19
1
Order By: Relevance
“…Using the sea urchin embryo model they showed that pharmacological inhibition of the corresponding efflux activity sensitized embryos to the toxic compound vinblastine, implying that one role for the efflux transport activity is embryo protection from xenobiotics. Likewise, follow-up studies reveal that polyspecific membrane transporters are required for signaling, homeostasis, and protection of the embryo 43 . In zebrafish, Fischer et al .…”
Section: Discussionmentioning
confidence: 99%
“…Using the sea urchin embryo model they showed that pharmacological inhibition of the corresponding efflux activity sensitized embryos to the toxic compound vinblastine, implying that one role for the efflux transport activity is embryo protection from xenobiotics. Likewise, follow-up studies reveal that polyspecific membrane transporters are required for signaling, homeostasis, and protection of the embryo 43 . In zebrafish, Fischer et al .…”
Section: Discussionmentioning
confidence: 99%
“…ABC transporters apply intracellular ATP hydrolysis, mediate drug efflux and protect cells from the damages induced by xenobiotics and toxins [17, 18]. Characteristics of this contributes a sort of critical mechanism of MDR in human malignancy, and members of this family are frequently over-expressed in cancer [19, 20].…”
Section: Discussionmentioning
confidence: 99%
“…129 Accordingly, recent tentative results of the in situ hybridization SUGSP database in S. purpuratus have demonstrated the expression of 82 genes in NSMCs. Three genes are expressed at the 10-hpf blastula stage, 65 genes are expressed in the period immediately before and during the EMT, and another 14 genes are expressed after the EMT (Table 3-1,2).…”
Section: The Emt In Nsmc and Nmc Formationmentioning
confidence: 99%